The Qur'anic ayah on wife beating : a comparative study on classical and modern interpretations - Noor Hafizah binti Dumi (Kulliyyah of Islamic Revealed Knowledge, International Islamic University Malaysia, 2015)
Islam continues to be a misunderstood religion especially to non-Muslims. Many of its directives remain a subject of hot debate, and continue to be a thorn in the minds of Muslim scholars. One of them is related to the Qurʼanic provision derived from the Quranic Ayah on wife beating, al-Nisaʼ 4: 34 that allows Muslim men to take action in dealing with their wives (women) whom they feared had committed disobedience, disloyalty and ill-conduct (nushuz); first, admonish them; second, if they remain disobedient and behave with ill-conduct, separate them from the beds; and third, if they refuse to amend their behaviour and are determined to demonstrate their disobedience and disloyalty, then subsequently the husbands may, therefore, beat them lightly (waaḍribuhunna). The first two steps of the action are reasonable and justified but the last one according to feminists and liberal Muslim authors, needs urgent reinterpretation because it looks like an incitement of violence against women. This research thus examines the wife beating phenomenon, particularly the one that occurs in Malaysia. It is then followed by analyzing the interpretations of selected classical and modern scholars in order to evaluate the differences between these two generations.